Fortifikasi Tepung Ikan Pada Cendol Sebagai Minuman Kaya Protein Di Desa Sungai Paku Kecamatan Kampar Kiri Kabupaten Kampar - Dewita Dewita; Desmelati Desmelati; Ayu Diana; Imelda Yunita; Muhammad Zakiyul Fikri; Santhy W. Sidauruk; Melania Syahada (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Indonesian society’s protein consumption remains low, particularly among lower-income groups. One strategy to improve protein intake is fortifying traditional foods. Cendol, a popular Indonesian beverage, was selected as the fortification medium using fish flour as a rich protein source. This community service project aimed to enhance nutritional knowledge, production skills, and public acceptance of fortified cendol with fish flour. The methods included nutrition education, a demonstration of fortified cendol preparation, and a simple organoleptic test. The results indicated an increase in participants’ knowledge of protein importance and positive acceptance of the fortified product. This innovation has the potential to support food security, improve nutrition, and create local food-based business opportunities.